Kort och gott. Om idiomens språkprov i Svensk ordbok utgiven av Svenska Akademien (2009) - Hult, Ann-Kristin (Nordiske Studier i Leksikografi, 2010)
In the recently published dictionary The Contemporary Dictionary of the Swedish Academy (2009), among other things, the selection of idioms has been revised. Also, the majority of idioms have been provided with examples. These have been extracted from various corpus resources, foremost from the dictionary project’s 240 million word corpus, but also from available press material on the Internet and through Google searches. This paper describes the principles of selecting and modifying authentic corpus evidence to good dictionary examples. In modifying the corpus examples we have considered factors such as length, degree of veracity, presence of proper nouns etc. There have sometimes been difficulties finding good examples to idioms with low corpus frequencies or phrases belonging to technical terminology. Moreover, lengthy examples are often difficult to avoid, as many idioms are long in themselves, or because their meaning calls for an extended example in order to illustrate their essence. With the corpus evidence as a basis, the aim has been to produce good dictionary examples which keep their character of naturalness and authenticity.